Correction: Proteomic analysis of the copper resistance of Streptococcus pneumoniae. Issue 12 (5th November 2015) - Guo, Zhong; Han, Junlong; Yang, Xiao-Yan; Cao, Kun; He, Ke; Du, Gaofei; Zeng, Guandi; Zhang, Liang; Yu, Guangchuang; Sun, Zhenghua; He, Qing-Yu; Sun, Xuesong
Abstract : Correction for 'Proteomic analysis of the copper resistance of Streptococcus pneumoniae ' by Zhong Guo et al., Metallomics, 2015, 7, 448–454.